(untitled) (Eurasian Journal of Ecology, 2025)
The article discusses the purification of water from pharmaceutical preparations (ceftriaxone) by sorption with a modified natural zeolite. The zeolite was modified with a surfactant (cetyltrimethylammonium bromide or CTAB) with different concentrations. In a study of the use of natural zeolite for wastewater treatment from pharmaceutical substances, it was found that the degree of adsorption reaches 97.3% for ceftriaxone, at an initial concentration of 50 mg/l. The adsorption isotherms corresponded to the Langmuir model, which confirms the high efficiency of zeolite in water purification from pharmaceutical pollutants and its potential for industrial applications. The results of the study confirm the prospects of using natural zeolites in water purification systems. Keywords: natural zeolite, modified zeolite, pharmaceutical substance, adsorption isotherm, adsorption kinetics, water purification